STUDY ON PROPAGATION AND GROWTH OF ARROWROOT (Maranta arundinaceae L.) AVAILABILITY IN A DIFFERENT LIGHT CONDITION - Wawo., dkk, Albert H. (BPPT)
Study on propagation and growth of arrowroot (Maranta arundinaceae L.) on different availability light condition. Arrowroot is a rhizome herbaceous plant that has potential as carbohydrate resources. The aims of this research are to use rhizome efficiently as material propagation on different availability light condition in order to get the best plant growth and arrowroot production. The research included 2 factors, which were internodes number of rhizome and shading, consisted of 6 combined treatments as factorial with Randomized Complete Design and three repetitions. The result of this research shown that by using 3 internodes of rhizome is the best material for propagation and produced the highest rhizome. The height of arrowroot was higher under shading than without shading. Arrowroot plants without any shading produced the highest fresh weight of rhizome compared to with 30% shading in Bogor condition.keywords: arrowroot, propagation, number of internode, shading.